Following tradition : folklore in the discourse of American culture - Bronner, Simon J. (UPCC book collections on Project MUSE., 1998)
Following Tradition is an expansive examination of the history of tradition--"one of the most common as well as most contested terms in English language usage"--In Americans' thinking and discourse about culture. Tradition in use becomes problematic because of "its multiple meanings and its conceptual softness." As a term and a concept, it has been important in the development of all scholarly fields that study American culture. Folklore, history, American studies, anthropology, cultural studies, and others assign different value and meaning to tradition.